Rock fracture under static stress conditions - Hoek, Evert (Department of Civil Engineering, 2016)
A knowledge of the strength of a material is an essential prerequisite to the successful design of a structure in that material. Consequently, in designing deep level mining excavations and large civil engineering structures, an understanding of the mechanics of rock fracture, particularly under compressive stress conditions, is of fundamental importance. This thesis contains details of an investigation into the applicability of Griffith's brittle fracture theory, modified to account for the effects of crack closure in compression, to the prediction of rock fracture behaviour. It is shown that this theory provides a reliable basis for the analysis of hard rock fracture under static stress conditions. The application of the Griffith's theory to the prediction of rock fracture initiation and propagation in a complex stress field is illustrated by means of a detailed analysis of the behaviour of the rock around a circular hole in a biaxial stress field. While this study is primarily concerned with rock fracture problems associated with deep level mining, it is believed that the general principles are equally useful in the analysis of rock and concrete fracture problems encountered in civil engineering.